Creativity in Project Based Learning: A Systematic Literature Study (2015-2021) - Purba, Leony Sanga Lamsari; Dasna, I Wayan; Habiddin, Habiddin (FKIP Universitas Lampung, 2022)
Character education has always been the focus of attention in the world of education in Indonesia. Creativity as an important form of character must really be measured with the right assessment instrument. Project Based Learning is a learning model that is able to explore the creativity of students. In this paper, a meta-review is conducted on the instruments for assessing student creativity in project-based learning on studies published in journals indexed by the Scopus database in 2011-2021. The results of this study show that the assessment of students' creativity in project-based learning by utilizing local wisdom has been widely carried out but has not found an assessment that focuses on all dimensions of creativity. In each PjBL syntax an assessment can be made, by adjusting the syntax to the creativity dimension which includes the dimensions of press, process, person, and product, but based on the results of the review there are no articles related to the implementation of PjBL based on local wisdom on the assessment of students' creativity, so the learning assessment only focuses on in the final condition does not include the learning process. Keywords: project based learning, creativity, systematic literature study. DOI: http://dx.doi.org/10.23960/jpmipa/v23i4.pp1504-1514